Maria-Aparecida Lopes (2022). Rio de Janeiro in the global meat market, c. 1850 to c. 1930. How fresh and salted meat arrived at the Carioca table - Farinatti, Luís Augusto (América Latina en la Historia Económica, 2022)
Sin resumen